أثر المسؤولية الاجتماعية على أداء المؤسسة الاقتصادية دراسة حالة شركة سوف للدقيق بالوادي - عادل مسعودي; أحمد بن ساعد; سماح بادة (جامعة الوادي University Of Eloued, 2024)
"ملخص هدفت هذه الدراسة إلى قياس أثر تبني المسؤولية الاجتماعية على أداء شركة سوف للدقيق، ومن أجل تحقيق ذلك تم الاعتماد على المنهج الوصفي التحليلي، باستعمال برنامج التحليل الاحصائي Spss اصدار 28، والمقابلات والزيارات الميدانية، كما تم اعداد وتوزيع استبيان حيث تكونت عينة الدراسة من 40 عاملا من مختلف الرتب، بينما تم اعتماد 36 استبيان فقط. ومنه توصلت الدراسة للنتائج التالية: يوجد دلالة ذات طبيعة احصائية لإلتزام المسؤولية الاجتماعية من طرف شركة سوف للدقيق حيث أثبتت الدراسة أن هذه العلاقة ترتكز أساسا على البعدين الخيري والأخلاقي، ومن جهة أخرى هناك علاقة ذات دلالة احصائية بين المسؤولية الاجتماعية وأداء شركة سوف للدقيق، حيث تبين أن هذه العلاقة مبنية على البعد المالي وبعد العمليات الداخلية، و هذا يدل على أن المسؤولية الاجتماعية للشركة أثرت في الأداء المالي من خلال الاستغلال الأمثل للموارد والالتزام بالمعايير المالية والمحاسبية المعمول بها، " " Abstract This study aimed to measure the impact of adopting social responsibility on the performance of Souf Flour Company. In order to achieve this, the descriptive analytical approach was relied upon, using the statistical analysis program Spss version 28, and interviews and field visits. A questionnaire was also prepared and distributed, and the study sample consisted of 40 workers. from various ranks, while only 36 questionnaires were approved. Hence, the study reached the following results: There is an indication of a statistical nature for the commitment to social responsibility on the part of the Sof Flour Company, as the study proved that this relationship is based mainly on the charitable and moral dimensions. On the other hand, there is a statistically significant relationship between social responsibility and the performance of the Sof Flour Company, as it was shown that this relationship is based on the dimension The financial and internal operations dimension, and this indicates that the company’s social responsibility affected the financial performance through optimal exploitation of resources and adherence to applicable financial and accounting standards, "
Keywords: المسؤولية الاجتماعية، تقييم الأداء، قياس الأداء، أبعاد المسؤولية الاجتماعية، أبعاد الأداء.; social responsibility; performance evaluation; performance measurement; dimensions of social responsibility; dimensions of performance